Copper Sulfide (CuxS) Nanowire‐in‐Carbon Composites Formed from Direct Sulfurization of the Metal‐Organic Framework HKUST‐1 and Their Use as Li‐Ion Battery Cathodes. (24th March 2018) - Foley, Sarah; Geaney, Hugh; Bree, Gerard; Stokes, Killian; Connolly, Sinead; Zaworotko, Michael J.; Ryan, Kevin M.
Abstract: Li‐ion batteries containing cost‐effective, environmentally benign cathode materials with high specific capacities are in critical demand to deliver the energy density requirements of electric vehicles and next‐generation electronic devices. Here, the phase‐controlled synthesis of copper sulfide (Cu x S) composites by the temperature‐controlled sulfurization of a prototypal Cu metal‐organic framework (MOF), HKUST‐1 is reported. The tunable formation of different Cu x S phases within a carbon network represents a simple method for the production of effective composite cathode materials for Li‐ion batteries. A direct link between the sulfurization temperature of the MOF and the resultant Cu x S phase formed with more Cu‐rich phases favored at higher temperatures is further shown. The Cu x S/C samples are characterized through X‐ray diffraction (XRD), thermogravimetric analysis (TGA), transmission electron microscopy, and energy dispersive X‐ray spectroscopy (EDX) in addition to testing as Li‐ion cathodes. It is shown that the performance is dependent on both the Cu x S phase and the crystal morphology with the Cu1.8 S/C‐500 material as a nanowire composite exhibiting the best performance, showing a specific capacity of 220 mAh g −1 after 200 charge/discharge cycles. Abstract : The phase‐controlled synthesis of copper sulfide (Cu x S) nanowire‐in‐carbon composites by the temperature‐controlled sulfurization of a prototypal Cu metal‐organic framework is developed. The tunable formation of different Cu x S phases within the carbon network demonstrates a facile method for the production of effective cathode materials for Li‐ion batteries.